PENGEMBANGAN ASESMEN FORMATIF TWO-TIER MULTIPLE CHOICE MENGGUNAKAN EDUCAPLAY PADA MATERI DATA DI SEKOLAH DASAR - Nawang Anggi Rahmawati; Ahmad Hariandi; Andi Gusmalia Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article aims to: (1) explain the validity level of two-level multiple-choice formative assessment using Educaplay on data material in elementary schools, (2) explain the reliability level of two-tier multiple-choice formative assessment using Educaplay on data material in elementary schools, (3) explain the practicality level of formative assessment using Educaplay on data material in elementary schools. The research approach used was Research and Development (R&D) with the DDD-E (Decide, Design, Develop, and Evaluate) model. This research was conducted at SDN 14/I Sungai Baung. The research data was obtained from observations, interviews, language, material, and media validation questionnaires, as well as feasibility questionnaires for teachers and students. The product validity level was evaluated by validators, with material validation obtaining a final score of 3.77 in the “valid” category, media validation 4.55 in the “very valid” category, and language validation 4.65 in the “very valid” category. The level of practicality of the product was obtained from the assessment of the teacher response questionnaire of 4.81 with the category of “very practical”, small group student responses of 4.6 with the category of “very practical”, and large group student responses of 4.4 with the category of “very practical”. Based on the final assessment of validity and practicality data, the developed product is suitable for use and can be utilized in the learning process in elementary schools.